Development of al-Qur’an Education and Learning Media at the al-Bahar Foundation, Tengket Village, Bangkalan Regency - Islamiyah; Abdurrohman; Ahmad Fawaid; As’adussholihin; Choirul Anam; Khoirul Anam (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2026)
Program pengabdian masyarakat is one form of academic contribution to society through various educational and empowerment-based activities. This community service activity was carried out in Tengket Village with a focus on strengthening religious education at al-Bahar Foundation. The programs implemented included teaching in non-formal educational institutions, teaching al-Qur’an reading, conducting community religious studies, creating social media platforms for the foundation, and developing a guidebook for learning to read the al-Qur’an. The method used in this program was a participatory approach through mentoring, teaching, and community education. The results of the activities showed an increase in community enthusiasm toward religious education, improved learning activities among the students, and the availability of learning media and digital documentation for the foundation. This program is expected to have a positive impact on improving the quality of religious education in the community of Tengket Village.